PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP RENTABILITAS PADA PT. SAMUDERA LAUTAN UTAMA - Paidi, Nur (DE FACTO : Journal Of International Multidisciplinary Science, 2023)
This paper intent to Know Influnce Likuiditas and Solvabilitas  to Rentabilitas to PT. Samudera Lautan Utama, Data collecting is done by use of interview and documentation. Analysis is data utilizes Analysis descriptive kualitatif.  The Result of this research that corporate Liquidity up to two the last year points out to mark sense ascensions Cash Ratio  as big as 16.32 %. that ascension because marks sense cash current asset affix and bank in year 2012, meanwhile Current Ratio  and Quick Ratio company experiences decrease each of 12.72 % for Current Ratio  and 8.89 % for Quick Ratio . Ratio is firm Solvency for year 2015 and 2014 still rank solvabel, still point out good situation for firm, but then argus-eyed regular and needs to mark sense corporate capital affix to increase more finance performance lovely at proximately. On year 2015 Ratio's Margin gross  experiencing ascension as big as 4.57 % it points out to mark sense cost-saving those aresued to get production result can be reached. Meanwhile for Operating is Ratio's Margin  experiencing decrease as big as 0,98 %.